CBT FOR SOCIAL ANXIETY DISORDER: CHILDHOOD EXPERIENCES AND BELIEF FORMATION: A CLINICAL CASE STUDY - Anam Bibi; Dr. Saima Dawood; Wajiha Ghazal; Aleena Khalid Ghori (International Journal of Contemporary Issues in Social Sciences, 2023)
Research on social anxiety disorder and its treatment especially cognitive behavioral approach focuses more on symptomatic nature and reduction. The present case study intends to highlight the significant childhood experiences resulting in belief formation that further activate during social interactions. Assessment of the client was done on both formal and informal levels. Clinical Interview was used as an informal way of assessment while Liebowitz Social Anxiety Scale, Social Interaction Anxiety Scale (SIAS) and Symptom Checklist-Revised were used as formal assessment tools. Analysis of scores and clinical interview lead to the diagnosis of 300.23 (F40.10) Social Anxiety Disorder with Mild Depressive Episode. Total number of 12 sessions were conducted with an average duration of 50 minutes for each session. It was found that childhood experiences play a significant role in developing certain beliefs later activated in social interactions and play a role in maintaining social anxiety disorder. Treatment focused more on these beliefs. Results indicated that CBT is an effective treatment approach for social anxiety disorder and treating maladaptive beliefs results in improved emotional and behavioral components of social anxiety disorder.